Propuesta pedagógica para formar lectores competentes desde las ciencias naturales (2021)
This research project aims to design a pedagogical proposal to train competent readers from the natural sciences in the Commercial and Industrial Technical Educational Institution of Palmar de Varela. It is exploratory in nature with a non-experimental design; because the studies are carried out without the deliberate manipulation of variables and in which the phenomena are only observed in their natural environment and then analyzed. A critical reading characterization test, a pretest questionnaire for students and teachers, and an open teacher interview were the instruments applied to collect information. The results obtained indicate that students have clear shortcomings to understand what they read, relate what they read with other texts, with their experience, knowledge, emotions or values. Likewise, it is difficult for them to infer information, predict, deduce or make critical judgments.